Investigation of charge transport in organic polymer donor/acceptor photovoltaic materials - Ahmad, Z.; Abdullah, S.M.; Zafar, Q.; Sulaiman, K. (Taylor & Francis, 2014)
pi-conjugated organic semiconductors have long been used as either holes or electrons transport materials. Recently, ambipolar charge carrier transport in these materials have been reported in many investigations. In this paper, we report on the basis of experimental results that the organic semiconductor (donor/acceptor) materials can be as good electrons transporters as these materials are holes transporters. In our study, the solution-processed unipolar diodes based on organic materials P3HT, VOPCPhO, and their blends with PCBM have been fabricated. The I-V characteristics of these diodes have been analyzed in the space-charge-limited current regime. The values of the electron and hole mobilities for the materials were found in the range of 10(-4)-10(-5)cm(2)/Vs.